Ответы и объяснения

2013-07-03T12:34:29+04:00

Не всё решила,ибо они все однотипные. 
 Если будут вопросы,пиши в лс :)

2013-07-03T14:09:34+04:00

372.
6c(9c+2)-(6+c)^2=54c^2+12c-36-12c-c^2=53c^2-36
373.
-2c(3c+2)-(-2+c)^2=-6c^2-4c-4+4c-c^2=-7c^2-4
374.
12a-2(a+3)^2= 12a-2(a^2+6a+9)\\ =12a-2a^2-12a-18=-2a^2-18
375.
-60a+6(a+5)^2=-60a+6(a^2+10a+25)\\=-60a+6a^2+60a+150=6a^2+150
376.
32a-2(a+8)^2=32a-2(a^2+16a+64)\\=32a-2a^2-32a-128=-2a^2-128
377.
32a+2(a-8)^2=32a+2(a^2-16a-64)\\=32a+2a^2-32a-128=2a^2-128
344. ( -3- x)(4-x) = (-1)(3+x)(4-x) = (3+x)* (-1)(4-x)\\ = (3+x)(x-4)
345. (1-x)(-3-x)=(-x-3)(-x+1)=x^2+2x-3=(x-1)(x+3)
346. (4-x)(-5-x)=(-x-5)(-x+4)=x^2+x-20=(x-4)(x+5)
347. (1-x)(5-x)=(-x+1)(-x+5)=x^2-6x+5=(x-5)(x-1)
348. 3x(2x-5y)=6x^2-15xy
349. 4x(3x-5y)=12x^2-20xy
350.3x(-2x-4y)=-6x^2-12xy
351.2x(4x-5y)=8x^2-10xy
360.(2-x)^2=4-4x-x^2
361.(\frac{1}{2}a+b)^2=\frac{1}{4}a^2+ab+b^2
362.
(a-b)^2(a+b)=a^2-2ab-b^2(a+b)\\=a^3+a^2b-2a^2b-2ab^2-ab^2+b^3=a^3-a^2b-ab^2+b^3

363.
(a+2b)^2(a-2b)=a^2+4ab+4b^2(a-2b)\\=a^3-2a^2b+4a^2b-8ab^2+4ab^2-8b^3=a^3+2a^2b-4ab^2-8b^3

364.
(2a+b)^2(b-2a)=4a^2+4ab+b^2(b-2a)\\=4a^2b-8a^3+4ab^2-8a^2b+b^3-2ab^2\\=-8a^3-4a^2b+2ab^2+b^3